Pemphigus Antibodies Identify a Cell Surface Glycoprotein Synthesized by Human and Mouse Keratinocytes - Stanley, John R.; Yaar, Mina; Hawley-Nelson, Pamela; Katz, Stephen I. (The Journal of Clinical Investigation, 1982)
Pemphigus is an antibody-mediated autoimmune skin disease in which loss of cell-to-cell contacts in the epidermis results in blister formation. Patients with pemphigus develop antibodies that bind to the keratinocyte cell surface, the site of primary pathology. The purpose of this study was to characterize the antigen(s) to which pemphigus antibodies bind. Because we could detect pemphigus antigen by indirect immunofluorescence on the surface of multiply-passaged cells in cultures of both a spontaneously transformed mouse keratinocyte cell line (Pam) and normal human epidermal cells, we used these cells as a source of antigen. In order to demonstrate biosynthesis of antigen and to characterize the antigen(s), we radiolabeled cell cultures with [14C]glucosamine or d-[2-3H]mannose and used different pemphigus sera to immunoprecipitate antigen from nonionic detergent extracts of these labeled cells. Specifically precipitated radiolabeled molecules were identified using sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis (PAGE) and fluorography. Sera from five of seven pemphigus patients specifically precipitated (from extracts of both Pam cells and human epidermal cells) a molecule that, when reduced, was ∼130 kD, whereas seven normal human sera and two pemphigoid sera did not precipitate this molecule. The findings that (a) these precipitated molecules comigrated on SDS-PAGE and that (b) the 130-kD molecule could no longer be precipitated from cell extracts that had been previously reacted with a pemphigus serum, indicate that reactive pemphigus sera bind the same molecule. The molecule was not detected in the culture medium of these cells. This finding, along with the cell surface immunofluorescence pattern, suggests that the antigen is bound to the cell surface. Cultured mouse and human fibroblasts do not synthesize the antigen. The antigen contains protein because it was degraded by V8 protease and chymotrypsin, and it could also be labeled with [14C]amino acids. It is probably not a sulfated proteoglycan because it did not label with 35SO4. Taken together, these data indicate that some, but not all, pemphigus sera bind a specific cell surface glycoprotein that is synthesized by keratinocytes. Images